Benefits of Electromagnetic Navigational Bronchoscopy for Identifying Pulmonary Nodules for Robotic Resections. Issue 6 (November 2017) - Pupovac, Stevan S.; Chaudhry, Alexander; Singh, Vijay A.
Objective: The ability to localize pulmonary nodules via the robotic thoracic technique can be challenging at times. This is most evident when nodules are small and/or ground glass in nature. Information regarding methods available to localize these difficult nodules, while maintaining a minimally invasive robotic approach, is limited. Methods: We describe a diagnostic and therapeutic method of combining electromagnetic navigational bronchoscopy with a total minimally invasive robotic approach that identifies these difficult-to-localize pulmonary nodules. The technique entails the use of electromagnetic navigational bronchoscopy to place a pleural dye marker with a subsequent pulmonary resection via a robotic thoracic approach. Results: A cohort of 15 patients from August 2014 to December 2015 was reviewed. These patients underwent the combined approach of electromagnetic navigational bronchoscopy followed by a robotic pulmonary resection. Fourteen of the 15 patients had a successful combined procedure, which was confirmed with pathology. The range of the nodules was 0.8 to 2 cm. Methylene blue was used for pleural dye marking. On one occasion, the pleural dye was not able to be deciphered. There were no complications from either the electromagnetic navigational bronchoscopy or robotic portions of the procedure. Conclusions: Pleural dye marking via electromagnetic navigational bronchoscopy can provide an effective method for localizing pulmonary nodules, while maintaining a minimally invasive robotic approach. This tactic allows one to obtain diagnostic tissue more efficiently, while limiting the potential inability to localize a nodule.